2018
DOI: 10.1242/jcs.216226
|View full text |Cite
|
Sign up to set email alerts
|

Rab4A organizes endosomal domains for sorting cargo to lysosome-related organelles

Abstract: Sorting endosomes (SEs) are the regulatory hubs for sorting cargo to multiple organelles, including lysosome-related organelles such as melanosomes in melanocytes. In parallel, melanosome biogenesis is initiated from SEs with the processing and sequential transport of melanocyte-specific proteins toward maturing melanosomes. However, the mechanism of cargo segregation on SEs is largely unknown. RNAi screening in melanocytes revealed that knockdown of Rab4A results in defective melanosome maturation. Rab4A-depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
(138 reference statements)
1
20
0
Order By: Relevance
“…Herein, we have demonstrated that Rab4A is a modulator of endocytic volume because Rab4A overexpression leads to increased endosomal size in both MCF10A and MDA-MB-231, whereas knockdown of Rab4A results in increased endosomal size in MCF10A but not in MDA-MB-231 cells. Previously, similar results have been shown in other cell types (59)(60)(61), suggesting that precise control of Rab4 expression regulates EE volume in a cell-specific manner. Considering that Rab4 has been shown to be involved in both membrane fusion and fission events (58,62), changes in Rab4 expression could result in increased EE size.…”
Section: Discussionsupporting
confidence: 83%
“…Herein, we have demonstrated that Rab4A is a modulator of endocytic volume because Rab4A overexpression leads to increased endosomal size in both MCF10A and MDA-MB-231, whereas knockdown of Rab4A results in increased endosomal size in MCF10A but not in MDA-MB-231 cells. Previously, similar results have been shown in other cell types (59)(60)(61), suggesting that precise control of Rab4 expression regulates EE volume in a cell-specific manner. Considering that Rab4 has been shown to be involved in both membrane fusion and fission events (58,62), changes in Rab4 expression could result in increased EE size.…”
Section: Discussionsupporting
confidence: 83%
“…Rab7 regulates formation of the late endosome, from which retromer, retriever and COMMD/CCDC22/CCDC93 (CCC)dependent cargo retrieval and recycling occurs (McNally et al, 2017;Purushothaman et al, 2017;Singla et al, 2019) or from which cargoes are directed to the lysosome for degradation (Guerra and Bucci, 2016). Rab4 is predominantly localized to the Rab5 + sorting endosomal compartment (Sönnichsen et al, 2000) and can regulate cargo transfer into both Rab11 recycling and cellular degradative pathways (McCaffrey et al, 2001;Nag et al, 2018). Little is known about the composition of membranes that recruit Rab4, however.…”
Section: Endosomal Sortingmentioning
confidence: 99%
“…For example, Rab6A and its effector ELKS regulate the transport of Dct from the trans ‐Golgi network (TGN) to melanosomes, and Rab6A‐melanocyte‐specific conditional KO mice exhibit hypopigmentation (Patwardhan et al., 2017). Rab4A and its two effectors are involved in the sorting of melanogenic enzymes on early endosomes (Nag et al., 2018), and Rab22A is involved in the biogenesis of tubular recycling endosomes through recruitment of BLOC‐1 and BLOC‐2, both of which are required for melanogenic enzyme transport (Shakya et al., 2018). Rab9A, which is present on early/recycling endosomes and melanosomes in melanocytes, also plays a role in delivery of melanosomal cargos (e.g., Tyr and Tyrp1) from syntaxin‐13‐positive recycling endosomes to melanosomes (Mahanty et al., 2016; Marubashi, et al., 2016).…”
Section: Rab Gtpases In Melanosome Biogenesis In Melanocytesmentioning
confidence: 99%